2015
DOI: 10.1097/rct.0000000000000282
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Segmentation of the Corpus Callosum Using a Cell-Competition Algorithm

Abstract: A cell-competition algorithm could be used to automatically evaluate callosal atrophy and tissue alterations. Assessments of the corpus callosal volume and tissue integrity helped to demonstrate the effects of CNS involvement in patients with SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…We also found that CCI was significantly lower in MS compared with SDCNS patients. Earlier studies showed that CCV is significantly lower in SLE-CNSI and SLE patients without CNS involvement than in healthy individuals both in adult [15,39,40,56,57] and pediatric populations [43]. In the work described above [15], the authors showed that the volume of the posterior part of CC is the best volumetric predictor distinguishing MS from SLE-CNSI patients.…”
Section: Discussionmentioning
confidence: 95%
“…We also found that CCI was significantly lower in MS compared with SDCNS patients. Earlier studies showed that CCV is significantly lower in SLE-CNSI and SLE patients without CNS involvement than in healthy individuals both in adult [15,39,40,56,57] and pediatric populations [43]. In the work described above [15], the authors showed that the volume of the posterior part of CC is the best volumetric predictor distinguishing MS from SLE-CNSI patients.…”
Section: Discussionmentioning
confidence: 95%
“…This can also partly explain the findings that NP-SLE patients seem to exhibit more disrupted WM integrities than non-NPSLE patients. 4,20,23,26,48 Disorders of the immune system might alter emotions and impair memories with specific brain structure injury mediated by antibody. 49,50 In SLE patients, the quantitative changes of brain parenchyma are not limited to neurons in the GM, but also influence the integrity of the WM tracts.…”
Section: Discussionmentioning
confidence: 99%
“…This can also partly explain the findings that NP-SLE patients seem to exhibit more disrupted WM integrities than non-NPSLE patients. 4,20,23,26,48…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations